A Comparative Analysis of Online Medical Record Utilization and Perception by Cancer Survivorship. Issue 12 (December 2020) - Khan, Saira; Lewis-Thames, Marquita W.; Han, Yunan; Fuzzell, Lindsay; Langston, Marvin E.; Moore, Justin X.
Abstract : Background: Cancer survivors face many challenges including coordinating care across multiple providers and maintaining medical records from multiple institutions. Access and utilization of online medical records could help cancer survivors manage this complexity. Here, we examined how cancer survivors differ from those without a history of cancer with regards to utilization and perception of medical records. Methods: We conducted a cross-sectional study of 3491 respondents, from the Health Information National Trends survey 5, cycle 2. The association of medical record utilization and perceptions with cancer survivorship was assessed using survey-weighted logistic regression. Results: Cancer survivors (n=593) were more likely to report that a provider maintains a computerized medical record [adjusted odds ratio (AOR)=2.05; 95% confidence (CI), 1.24–3.41] and were more likely to report confidence in medical record safeguards (AOR=1.44; 95% CI, 1.03–2.03). However, cancer survivors were no more likely to access online medical records than those without a history of cancer (AOR=1.13; 95% CI, 0.69–1.86). Cancer survivors were no more likely to report privacy concerns as a reason for not accessing online medical records, however, survivors were more likely to report a preference for speaking directly with a provider as a reason for not accessing online medical records (AOR=2.24; 95% CI, 0.99–5.05). Conclusions: Although cancer survivors are more likely to trust medical record safe guards and do not express increased concerns about online medical record privacy, a preference to speak directly with provider is a barrier of use. Abstract : Supplemental Digital Content is available in the text.